Formación contable en Chile “una propuesta de articulación curricular” - Gallegos Muñoz, Cecilia; Rodríguez Quezada, Estela (Universidad de Costa Rica, 2017)
The vertical articulation promotes the access of the students of secondary education to higher education; it also allows them to move smoothly between these two formative levels, through the recognition of previously acquired learning. In this context, the objective of this article is to determine the feasibility of a vertical articulation between the Professional Technical Colleges that offer the title of average level in Accounting in the Maule and Bío-Bío region and the Universities of the same regions that offer the Career of Public Accountant and / or Auditor in Chile in order to establish a model or proposal of curricular articulation between these two formative levels. From the methodological point of view, a comprehensive analysis of the curricula of these institutions was carried out to establish an effective articulation model. The proposal considers articulating at least six subjects, one from each training area, which would have to be taken by the students during the secondary education and all the Universities should offer during the first semester. This would allow the students of average education to validate the acquired learning and with this, to reduce the time of permanence in Higher Education to promote an early exit to the labor market.